ANALISIS KESULITAN BELAJAR SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI PEMBAGIAN KELAS IV DI SD NEGERI NGABEAN PURWOREJO - Risma Fardlila; Suyoto; Arum Ratnaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the learning difficulties experienced by students insolving and describe the factors causing students learning difficulties in solvingstory problems on division material in grade IV of Ngabean State ElementarySchool. This research method uses a qualitative descriptive type by describing theresults of research in grade 4 with a total of 5 students as subjects. Data collectiontechniques and instruments were observation, interviews, documentation, anddata recording cards. Data analysis techniques used were data collection, datareduction, data presentation, and drawing conclusions. The results of the initialstudy showed that students: (1) had difficulty understanding the concept, studentswere able to understand the concept of division, this occurred in AA, SA, and MAI(2) difficulty applying the principle, students were unable to use the arithmeticoperation of division to apply it to nested division, which occurred in AA and MAIand (3) difficulty solving verbal problems, students were unable to solve the storyproblems using the steps that occurred in AA, MAI, NW, SA, and SS. Based onthe results of this analysis, it was concluded that students experienced learningdifficulties. Second, these learning difficulties are caused by two main factors,namely: (1) internal factors, such as interest and motivation to learn, talent,attitudes towards learning, lack of teacher understanding of learning methods, and(2) external factors, such as family environment, school environment, peers, theinfluence of mass media, and learning tools.